Evidence‐based region of interest (ROI) definition for surface‐guided radiotherapy (SGRT) of abdominal cancers using deep‐inspiration breath‐hold (DIBH). Issue 11 (10th August 2022) - Song, Yulin; Zhai, Xingchen; Liang, Yubei; Zeng, Chuan; Mueller, Boris; Li, Guang
Abstract: To define and evaluate the appropriate abdominal region of interest (ROI) as a surrogate of diaphragm positioning in deep‐inspiration breath‐hold (DIBH) for surface‐guided radiotherapy (SGRT) of abdominal cancers using 3D optical surface imaging (OSI). Six potential abdominal ROIs were evaluated to calculate their correlations with the diaphragm position using 4DCT images of 20 abdominal patients. Twelve points of interest (POIs) were defined (six on the central soft tissue and six on the bilateral ribs) at three superior–inferior levels, and different sub‐groups represented different ROIs. ROI‐1 was the largest, containing all 12 POIs from the xiphoid to the umbilicus and between the lateral body midlines while ROI‐2 had only eight inferior POIs, ROI‐3 had six lateral POIs, and ROI‐4 had four superior‐lateral POIs over the ribs, ROI‐5 contained six central and two most inferior‐lateral POIs and ROI‐6 contained six central and four inferior‐lateral POIs. Internally, the right diaphragm dome was used to represent its positions in 4DCT (0% and 50% within the cycle). The Pearson correlation coefficients were calculated between the diaphragm dome and all 12 external POIs individually or grouped as six ROIs. The quality of the abdominal ROIs was evaluated as potential internal surrogates and, therefore, potential ROIs for SGRT DIBH setup. The four most inferior POIs show the highest mean correlation ( r = 0.75) with diaphragmatic motion, and the correlation decreases as POIs move superiorly. The mean correlations are the highest for ROIs with little or no rib support: r = 0.67 for ROI‐2, r = 0.64 for ROI‐5, and r = 0.63 for ROI‐6, while lower for ROIs with rib support: ROI‐1 has r = 0.60, ROI‐3 has r = 0.50, and ROI‐4 has only r = 0.28. This study demonstrates that the rectangular/triangular soft‐tissue ROI (with little rib support) is an optimal surrogate for body positioning and diaphragmatic motion, even when treating tumors under the rib cage. This evidence‐based ROI definition should be utilized when treating abdominal cancers with free‐breathing (FB) and/or DIBH setup.